Chitosan as a smart coating for corrosion protection of aluminum alloy 2024: A review - Carneiro, J.
In this work we review results obtained using chitosan as a coating to protect aluminum alloy 2024. Different inhibitors were added to the matrix, interaction between inhibitor and functional groups from chitosan investigated and functionalization of chitosan performed in the bulk, as well as at the coating/solution interface to improve the barrier properties. The obtained systems were characterized by proton-nuclear magnetic resonance (H-1 NMR), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The protective performance was monitored using electrochemical impedance spectroscopy (EIS) and the scanning vibrating electrode technique (SVET). Overall, the obtained results support the possibility of using inhibitor-loaded chitosan systems to protect metallic substrates, either as components in multi-layer coatings systems, or as free-standing films. (C) 2015 Elsevier B.V. All rights reserved.